1995
DOI: 10.1021/bi00022a010
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament-associated protein phosphatase 2A: Its possible role in preserving neurofilaments in filamentous states

Abstract: Neurofilament phosphatase (NF-phosphatase) activity, which dephosphorylates NF proteins phosphorylated by cyclic AMP-dependent protein kinase (A-kinase), was detected in NF fractions prepared from bovine spinal cords. This phosphatase was suggested to be associated with NFs by gel filtration and sedimentation analysis and was further demonstrated by dephosphorylation-dependent binding assay of NFs to microtubules. The NF-associated NF-phosphatase was identified as a type of protein phosphatase 2A (PP2A) by (i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 57 publications
4
46
0
1
Order By: Relevance
“…Our observations coincide with a number of recent studies documenting PP-2A association with different kinases [12][13][14][15][16][17][18][19][20][21][22]. For example, studies by Heriche et al [12] indicate that casein kinase 2α associates with PP-2A and causes activation of PP-2A.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our observations coincide with a number of recent studies documenting PP-2A association with different kinases [12][13][14][15][16][17][18][19][20][21][22]. For example, studies by Heriche et al [12] indicate that casein kinase 2α associates with PP-2A and causes activation of PP-2A.…”
Section: Discussionsupporting
confidence: 92%
“…For example, PP-2A has been shown to bind the β2-adrenergic receptor [11], casein kinase 2α [12], homeobox gene 11 [13], tau [14], translation termination eukaryotic release factor 1 [15], adenovirus e4orf4 protein [16], α4 protein [17], neurofilament proteins [18,19] and small t and middle t antigens encoded by DNA tumour viruses [20,21]. Recent studies by Westphal et al [22] identified a calmodulin IV (CaMIV)-PP-2A complex in which PP-2A dephosphorylates…”
Section: Introductionmentioning
confidence: 99%
“…PP2A is the major protein phosphatase acting on neurofilaments and found associated with this type of IF (Saito et al, 1995). To corroborate an association of PP2A with vimentin, fractions highly enriched in IFs were prepared from Hs68 fibroblasts ( Figure 7A) and immunoblotted for the presence of PP2A subunits.…”
Section: Pp2a Association With Vimentinmentioning
confidence: 92%
“…We have previously reported that cytokeratins 8 and 18 become hyperphosphorylated when type 2A but not type 1 enzymes are inhibited . PP2A was also identified as a neurofilament phosphatase and, significantly, associates with this type of IF (Saito et al, 1995). Whether PP2A is always targeted to IF by B55 remains to be established.…”
Section: Role Of If Dephosphorylation By Pp2amentioning
confidence: 99%
“…On the other hand, there are examples that assembly of filaments is as well as regulated by phosphorylation and dephosphorylation. Neurofilaments are major intermediate filaments expressed in neurons, and their assembly is regulated by phosphorylation and dephosphorylation (Gonda et al , 1990;Saito et al , 1995). Reorganization of vimentin and glial fibrillary acidic protein during mitosis are also regulated by phosphorylation (Inagaki et al , 1987;Matsuzawa et al , 1995).…”
Section: Discussionmentioning
confidence: 99%